Vortex dynamics simulation for pinning structure optimization in the applications of high-temperature superconductors. (8th June 2022) - Rivasto, E; Huhtinen, H; Hynninen, T; Paturi, P
Abstract: We introduce a molecular dynamics based simulation model that enables the efficient optimization of complex pinning structures in unpresented wide magnetic field and angular ranges for high-temperature superconductor applications. The fully three-dimensional simulation allows the modeling of the critical current and the associated anisotropy in the presence of any kinds of defects despite their size and orientation. Most prominently, these include artificial defects such as nanorods along with intrinsic weak-links or ab -plane oriented stacking faults, for example. In this work, we present and analyze the most fundamental results of the simulation model and compare them indirectly with a wide range of previous experimental and computational observations. With the provided validation for the proposed simulation model, we consider it to be an extremely useful tool in particular for pushing the limits of ampacity in the coated conductor industry.